1995
DOI: 10.1590/s0102-311x1995000100021
|View full text |Cite
|
Sign up to set email alerts
|

Aids em crianças: considerações sobre a transmissão vertical

Abstract: the epidemiological aspects of the acquired immunodeficiency syndrome (AIDS) in children and the vertical transmission of the human immunodeficiency virus (HIV). The modes of mother-to-infant transmission are discussed, including physiopathological aspects of HIV infection in utero, during, and/or after delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
8

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
0
5
0
8
Order By: Relevance
“…The first report about childhood-acquired immunodeficiency syndrome (AIDS) was described in 1982 [1]. Since then, the increase in heterosexual transmission has resulted in a higher incidence of cases among women and a consequent increase in vertical transmission.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first report about childhood-acquired immunodeficiency syndrome (AIDS) was described in 1982 [1]. Since then, the increase in heterosexual transmission has resulted in a higher incidence of cases among women and a consequent increase in vertical transmission.…”
mentioning
confidence: 99%
“…Since then, the increase in heterosexual transmission has resulted in a higher incidence of cases among women and a consequent increase in vertical transmission. About 75%-85% of infected children acquire human immunodeficiency virus (HIV) through this pathway; 20%-25% through blood transfusion or blood products; in older children and adolescents, HIV is acquired through sexual transmission or use an intravenous drug needles [1][2]. In 2000, Szwarcwald et al estimated that 12,800 children 0-14 years-old were infected by HIV in Brazil and that 1,968 were born alive with HIV [3].…”
mentioning
confidence: 99%
“…Because of that, mothers are advised to suspend the breast-feeding (Brazil, 2006). However, Ortigão (1995) discusses that mother's milk could be the single nutritional source for the nursling in low revenue families, making that the risk to take HIV becomes less relevant than the risk of death due to innutrition. This author quotes that the World Health Organization (WHO) recommends that in countries where infectious diseases and innutrition are the main causes for child mortality, the breast-feeding should be recommended for all mothers, including the ones with HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the placental membrane constitutes an important barrier between mother and fetus (Ortigão 1995). A recent study found that cells from placental membranes of non-transmitters were not infected by HIV-1, although lymphocytes present within the placentas were HIV-1 positive (Tscherning-Casper et al 1999).…”
Section: Mother's Health and Genotypementioning
confidence: 99%